Class Action Suit Seeking Equal Rights for Female Swimmers: Editor: Thomas H. Sawyer. Issue 4 (3rd May 2020) - Sawyer, Tonya L.
Abstract : This case examines a class action suit brought by members of a high school swim team in Hawaii alleging several violations of Title IX.